Pseudo-Stieltjes calculus: $ α- $pseudo-differentiability, the pseudo-Stieltjes integrability and applications - Caiqin Wang; Hongbin Xie; Zengtai Gong (Electronic Research Archive)
In this paper, the concepts of the $ α- $pseudo-differentiability and the pseudo-Stieltjes integrability are proposed, and the corresponding transformation theorems and Newton–Leibniz formula are established. The obtained results provide a framework for analyzing nonlinear differential equations.